Immediate and Delayed Feedback and Their Effect on Learning Freestyle Swimming Movements for Beginner Students - Salah alddin, Mustafa; Mansor, Samir (Journal of Physical Education, 2018)
Immediate and Delayed Feedback and Their Effect on Learning Freestyle Swimming Movements for Beginner Students The problem of the research was that the researchers noticed through the practical lessons of swimming class that there is a great variation in the grades of the students in the different study subjects according to the teaching of the section which may be due to the difference in how each teacher gives the corrective information, From one teaching to the next, which may be the reason for this variance between the levels of learners at the end of the academic season Thus, the present study aimed at finding the effect of using immediate and delayed feedback on the level of learning freestyle swimming movements in the subjects understudy. In addition to that, the research aimed at identifying the two types of feedback used (immediate and delayed) in learning freestyle swimming movements in the subjects. The researcher used the experimental method and the subjects were students of the physical education and sport Science College / University of Baghdad. The researchers concluded that immediate and delayed feedback has positive effects on learning freestyle swimming movements. Immediate feedback in the experimental group was better than the controlling group in the post-tests.